Improving Knowledge and Skills in Healthy Agro-Marine Food Processing among Indonesian Immigrant Communities in Malaysia - Muhammad Yusuf; Eny Winaryati; Budi Santosa; Hardiwinoto Hardiwinoto; Edy Purwanto; Andwiani Sinarasri; Nurrahman Nurrahman; Yunan Kholifatuddin Sya’di; Masrukhi Masrukhi; Siti Zaharah Rosli (Universitas Muhammadiyah Semarang, 2026)
Fish and other agro-marine products are important sources of high-quality protein, essential amino acids, omega-3 fatty acids, vitamins, and minerals. However, immigrant communities may experience changes in dietary habits due to limited access to familiar food ingredients, affordability issues, and adaptation to new food environments. This community service program aimed to improve nutritional literacy and practical skills in healthy agro-marine food processing among Indonesian immigrant communities in Kuala Lumpur, Malaysia. The program was conducted in June 2024 through collaboration among Management and Science University, Universiti Muhammadiyah Malaysia, the Muhammadiyah Special Branch (PCIM) of Malaysia in Kuala Lumpur, and the community service team. The activity involved 20 participants and was implemented through five stages: socialization, practical training, technology application, evaluation assistance, and sustainability planning. Program outputs included nutrition education on fish consumption, demonstrations of healthier processing methods such as steaming, boiling, and grilling, introduction of fish-product diversification, utilization of agro-marine by-products, a processing guidebook, and digital learning materials. Evaluation through observation, discussion, and participant feedback indicated that the program helped participants understand the nutritional value of fish and recognize healthier and more economically productive processing alternatives. Continuous mentoring is recommended to strengthen long-term dietary improvement and community-based entrepreneurship.